Factors that influence attitude towards ICT usage among rural community leaders in Malaysia - D’ Silva, Jeffrey Lawrence; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Abu Hassan, Musa (American-Eurasian Network for Scientific Information, 2010)
Rural communities in Malaysia have been encouraged to develop themselves with ICT skills and knowledge. Mega ICT projects such as Rural Internet Center, Rural Info Center and National Broadband Initiatives have been introduced to encourage rural people to use ICT. To encourage rural people to use ICT, they must have positive attitude towards it and this study would specifically investigate the rural community leaders attitude towards ICT usage. This is a quantitative study. A total of 240 rural community leaders comprising Village Development and Security Committee were selected as the respondents. Using SPSS, descriptive and inferential analyses were performed to fulfill the objectives determined. Based on the results gained, it can be concluded that Village Development and Security Committee have a moderate level of attitude towards ICT usage. It was also identified that the self-efficacy, perceived usefulness, perceived ease of use, subjective norm, compatibility and job relevance have positive and significant association with attitude towards ICT usage. Further analysis done have proved that self-efficacy was the major significant contributor for attitude towards ICT usage. To further develop Village Development and Security Committee attitude towards ICT, it is recommended that rural community access and exposure to ICT must be strengthened.